2018
DOI: 10.2166/wst.2018.409
|View full text |Cite
|
Sign up to set email alerts
|

Survival of ESKAPE pathogen Acinetobacter baumannii in water of different temperatures and pH

Abstract: Bacterium Acinetobacter baumannii is an emergent pathogen associated with nosocomial infections, which can be also found in natural waters. The impact of ecological factors on A. baumannii is insufficiently investigated. The aim was to examine the influence of temperatures (−20 to 80 °C) and pH values (2 to 12) on the survival of environmental and clinical isolates of A. baumannii in nutrient-deprived spring water (SW) and nutrient-rich diluted nutrient broth during 5 months. A. baumannii successfully survived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…The bacteria did not multiply, probably due to low soil organic carbon content (0.215 wt%). An earlier study ( 11 ) showed that A. baumannii survived for a long time (150 days) in spring water with a pH of 8.1, which is very close to the pH of our red palaeosol samples (8.43±0.14). As moisture was kept to the maximum water holding capacity, desiccation can be eliminated as the cause of A. baumannii count drop.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The bacteria did not multiply, probably due to low soil organic carbon content (0.215 wt%). An earlier study ( 11 ) showed that A. baumannii survived for a long time (150 days) in spring water with a pH of 8.1, which is very close to the pH of our red palaeosol samples (8.43±0.14). As moisture was kept to the maximum water holding capacity, desiccation can be eliminated as the cause of A. baumannii count drop.…”
Section: Resultssupporting
confidence: 88%
“…Rises and falls in A. baumannii counts observed from day 68 on could be explained by the “bust and boom” survival strategy, where weak cells die to provide sustenance for the remaining cells ( 9 ). However, the difference between the 32 % survival in red palaeosol in this study and >90 % survival in spring water in our earlier study ( 11 ) suggests that nutrient deprivation is not the only cause of lower A. baumannii survival in red palaeosol. Perhaps it was the presence of Fe in wet red palaeosol that contributed to the drop in A. baumannii count via oxidative stress ( 20 ).…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Reduction of the acyl chain length would decrease the Van der Waals molecular interactions between neighboring LPS molecules, resulting in a more fluid membrane ( 2 , 43 ). Although associated primarily with hospital-acquired infections ( 44 ), A. baumannii can be found in a variety of reservoirs ( 45 , 46 ) with environmental isolates capable of surviving in a wide range of temperatures for prolonged periods of time, including in the cold ( 47 ). Thus, the bacterium must be able to maintain membrane fluidity under a variety of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter baumannii has been linked to respiratory infection, pneumonia, and urinary tract infections (Tiwari et al., 2015). The bacteria can be also found in untreated water (Dekic et al., 2018). Antibiotic‐resistant bacteria recovered from lettuce treated with gentamicin included Delftia sp, Cupriavidus pauculus, Sphingobacterium changzhouense, and Ralstonia insidiosa .…”
Section: Resultsmentioning
confidence: 99%